Peer effects and teacher absences - Campos, Bruno Garcia (2017)
Teacher quality is of critical importance in student achievement. In addition to previous training, experience and teaching methodologies, teacher assiduity plays a pivotal role in pupils' development. In this paper, we investigate how teacher absences are influenced by their colleagues at work. More specifically, we try to answer if there are peer effects behind teachers’ behavior. We resort to a model of instrumental variables to isolate the causal impact from potential identification problems arising from endogenous group formation and estimate a positive, significant peer effect of teacher absences on those of their colleagues. Additionally, we explore how teachers under different contract regimes are affected, and show peer effects are not linear – what suggests the existence of an optimal allocation of teachers that minimizes collective absences. Furthermore, we show teachers exert discretion on absences, and that this kind of absences are what mainly drives our results.